IoT-Enabled Integrated Smart Wound Sensor for Multiplexed Monitoring of Inflammatory Biomarkers at the Wound Site - Noushin, Tanzila; Hossain, Nafize Ishtiaque; Tabassum, Shawana (Frontiers in Nanotechnology, 2022)
Chronic wounds that stall at the inflammatory phase of healing may create several life-threatening complications such as tissue damage, septicemia, and organ failures. In order to prevent these adverse clinical outcomes and accelerate the wound healing process, it is crucial to monitor the wound status in real-time so that immediate therapeutic interventions can be implemented. In addition, continuous monitoring of the wound status prevents drug overdose at the wound site, leading to on-demand and personalized drug delivery. Inflammatory mediators, such as Interleukin-6 (IL-6) and Interleukin-10 (IL-10) are promising indicators for the progression of wound healing and predictors of disease severity. Toward this end, this work reports a flexible wound patch for multiplexed monitoring of IL-6 and IL-10 at the wound site in order to provide real-time feedback on the inflammation phase of the wound. An optimized composition of gold nanoparticles integrated multiwalled carbon nanotube was demonstrated to improve sensor performance substantially. The sensor also exhibited excellent repeatable, reversible, and drift characteristics. A miniaturized Internet-of-things (IoT)-enabled potentiostat was also developed and integrated with the flexible sensor to realize a wearable system. This IoT-enabled wearable device provides a smart and cost-effective solution to improving the existing wound care through continuous, real-time, and in-situ monitoring of multiple wound biomarkers.